Dominica. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Dominica during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as protected agriculture, production, greenhouse, water management, plant nutrition, training, agrotourism, food security, health and safety, financing and food processing. Finally, work was done on the use of pesticides, nurseries, seedlings, technology, international market, fruit drying, biogas, pest and disease control, inclusion of women, pig and vegetable production.